The business of fine art photography art markets, galleries, museums, grant writing, conceiving and marketing your work globally - Werner, Thomas (Photographer) (Routledge, an imprint of the taylor & Francis Group, 2023)
This guide for aspiring and exhibiting photographers alike combines practice and concept to provide a roadmap to navigating and succeeding in the fine art photography marketplace locally, domestically, and internationally. Join former New York gallery owner, international curator, and fine art photographer Thomas Werner as he shares his experiences and insights from leading curators, gallerists, collectors, auctioneers, exhibiting photographic artists, and more. Learn how to identify realistic goals; maximize results; work with galleries and museums; write grants; develop strong nuanced imagery; and build a professional practice in a continually evolving field. Featuring dozens of photographs from international practitioners, sample activities, and a robust set of resources, this book will ensure you have the tools to give you the opportunity for success in any marketplace. Whether you are a student, aspiring photographic or video artist, or a photographer changing careers The Business of Fine Art Photography is your guide to starting and growing your own practice"--Provided by publisher.